Futurismo e futurismi. - Hulten, P. (Milan : Bompiani, 1986)
Adrian-Nilsson, Gösta ; Alva de la Canal, Ramón ; Archipenko, Aleksandr ; Atkinson, Lawrence ; Balla, Giacomo ; Baranoff-Rossine, Wladimir ; Barradas, Rafael ; Bendetta ; Boccioni, Umberto ; Bomberg, David ; Bortnyik, Sándor ; Bragaglia, Anton Giulio ; Bragaglia, Arturo ; Braque, Georges ; Burljuk, David ; Burljuk, Vladimir Davidovic ; Cangiullo, Francesco ; Capek, Josef ; Carrà, Carlo ; Chagall, Marc ; Charlot, Jean ; Chiattone, Mario ; Chwistek, Leon ; Ciurlionis, Mikalojus Konstantinas ; Conti, Primo ; Cramer, Konrad ; Csáky, József ; Cueto, Germán ; Cursiter, Stanley ; Czyzewski, Tytus ; Daugherty, James H. ; Delaunay, Robert ; Delaunay, Sonia ; Delmarle, Felix ; Demuth, Charles ; Depero, Fortunato ; Dismorr, Jessica ; Diulgheroff, Nicola ; Dix, Otto ; Dottori, Gerardo ; Dove, Arthur G. ; Dr. Atl ; Duchamp, Marcel ; Duchamp-Villon, Raymond ; Dudreville, Leonardo ; Ender, Boris ; Ender, Ksenia ; Epstein, Jacob ; Ernst, Max ; Etchells, Frederick ; Exter, Alexandra ; Farfa ; Fauconnier, Henri Le ; Feuerstein, Bedrich ; Fillia ; Filonov, Pavel ; Fry, Roger ; Gaudier-Brzeska, Henry ; Giacometti, Augusto ; Gleizes, Albert ; Goncharova, Natalia ; Gotlib, Henryk ; Grosz, George ; Gutfreund, Otto ; Hartley, Marsden ; Hrynkowski, Jan ; Hulewicz, Jerzy ; Joostens, Paul ; Kallenborn, Joseph ; Kanbara, Tai ; Kandinsky, Wassily ; Kroha, Jiri ; Kubista, Bohumil ; Kupka, Frantisek ; Langdon Coburn, Alvin ; Larionov, Michail ; Laurens, Henri ; Leal, Fernando ; Leger, Fernand ; Lumière Brothers ; MacDonald-Wright, Stanton ; Magnelli, Alberto ; Majakovskij, Vladimir ; Malevich, Kasimir ; Marc, Franz ; Marchi, Virgilio ; Marey, Etienne-Jules ; Marin, John ; Marinetti, Filippo Tommaso ; Matiushin, Mikhail ; Méliès, Georges ; Melli, Roberto ; Méndez, Leopoldo ; Munch, Edvard ; etc.
boek